2019
DOI: 10.1111/1467-8551.12299
|View full text |Cite
|
Sign up to set email alerts
|

Does Board Ethnic Diversity Impact Board Monitoring Outcomes?

Abstract: This study investigates whether board ethnic diversity is associated with stronger board monitoring outcomes. We explore a range of outcomes -CEO compensation, accounting misstatements, CEO turnover-performance sensitivity and acquisition performance -but find no evidence to support this. We also find no evidence that board ethnic diversity improves overall firm performance, even for those firms with higher agency problems. Our results are robust across different methodologies and have important practical impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 78 publications
(158 reference statements)
3
79
2
Order By: Relevance
“…The existing literature suggests that diversity of the board of directors and its committees are considered as one of the most effective ways to enhance corporate governance (Carter et al , 2010; Cheong and Sinnakkannu, 2014; Scholtz and Kieviet, 2018). In the aftermath of the global financial crisis of 2008, there is an increase in calls for diversity on corporate boards because it is claimed that the lack of board diversity may be partly to blame for the crisis (Anderson et al , 2011; Beattie et al , 2012; Guest, 2019). Thus, diversity on corporate boards has received significant attentions from regulators, media and academics (Bernile et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature suggests that diversity of the board of directors and its committees are considered as one of the most effective ways to enhance corporate governance (Carter et al , 2010; Cheong and Sinnakkannu, 2014; Scholtz and Kieviet, 2018). In the aftermath of the global financial crisis of 2008, there is an increase in calls for diversity on corporate boards because it is claimed that the lack of board diversity may be partly to blame for the crisis (Anderson et al , 2011; Beattie et al , 2012; Guest, 2019). Thus, diversity on corporate boards has received significant attentions from regulators, media and academics (Bernile et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The ineffectiveness resulting from larger board are attributed to communication barrier when there are too many people involved in the decision-making process therefore, Apriliyanti and Randøy (2019) suggested that the number of BoD should be limited to ten (Apriliyanti and Randøy, 2019). Guest (2019) found out that smaller boards produce stringer returns, have stronger oversight, always more favorable (Guest, 2019). Australian Institute of Company Directors indicated that large listed companies should have 8 to 12 directors, medium-sized listed companies 6 to 8 directors and small listed companies 4 to 6 directors (Dias, Rodrigues, Craig, and Neves, 2019).…”
Section: Board Size and Bank Financial Stabilitymentioning
confidence: 99%
“…Guest (2019) explores the effects of board ethnic diversity on the monitoring intensity provided by the board of directors. Guest (2019) explores the effects of board ethnic diversity on the monitoring intensity provided by the board of directors.…”
Section: Boards Of Directorsmentioning
confidence: 99%
“…Conyon et al (2019) revisit the effects of compensation consultants on levels of executive pay and payperformance sensitivity. Guest (2019) and Jelic et al (2019) focus on board monitoring, by studying board ethnic diversity and secondary management buyout boards, respectively. Conyon et al (2019) study the effects of compensation consultants in UK firms from the FTSE All-Share Index during the period 2003-2011.…”
Section: Boards Of Directorsmentioning
confidence: 99%
See 1 more Smart Citation